2003
DOI: 10.1128/jvi.77.21.11616-11624.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Mumps Virus Gene Sequence Associated with Variability in Neurovirulent Phenotype

Abstract: Mumps virus is highly neurotropic and, prior to widespread vaccination programs, was the major cause of viral meningitis in the United States. Nonetheless, the genetic basis of mumps virus neurotropism and neurovirulence was until recently not understood, largely due to the lack of an animal model. Here, nonneurovirulent (Jeryl Lynn vaccine) and highly neurovirulent (88-1961 wild type) mumps virus strains were passaged in human neural cells or in chicken fibroblast cells with the goal of neuroadapting or neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In the HN protein of the Kilham strain (GB. AY502062), histidine and serine were found at aa354 and 356, which might be associated with mumps neurovirulence [20]. Such changes, however, were not found in any strain investigated in this study (Figure 1), except for proline and glutamic acid, which were at aa354 and 356, respectively, of some historic strains, which belonged to genotype A (Figure 1).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In the HN protein of the Kilham strain (GB. AY502062), histidine and serine were found at aa354 and 356, which might be associated with mumps neurovirulence [20]. Such changes, however, were not found in any strain investigated in this study (Figure 1), except for proline and glutamic acid, which were at aa354 and 356, respectively, of some historic strains, which belonged to genotype A (Figure 1).…”
Section: Resultsmentioning
confidence: 65%
“…Strain 88-1961, a wild-type strain isolated from a patient with neurological symptoms, caused severe, devastating neurological damage (e.g., hydrocephalus) in the rat neurovirulence assay [12]. The serine→asparagine substitution at aa466 in the HN of strain 88-1961 (Table 1), which is predicted to result in a loss of N glycosylation site (aa464 to aa466) had the potential to affect virus tropism and virulence, and was associated with an aa change in the L protein with MuV neuroattenuation [20], [36], [37]. However, in the present study, the above-mentioned substitutions in the HN gene were not found in the 39 sequences generated in the P and N groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that amino acid substitutions at positions 335, 354, 356, 360, 464, and 466 in the HN region, and in positions 29 and 48 in the SH region, resulted in neuro-virulence of the virus. [19,42,43] The HN region is the main immunogenic part of the mumps genome and contains glycosylation sites in 3 epitope domains (aa265-288, aa329-340, aa352-360). [19] The SH region is the most variable part of the genome and is used for genotyping as well as for phylogenetic analysis of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The controversial Urabe strain for mumps, whose use stopped as a vaccinating strain because of developing meningitis and encephalitis (19), was produced by attenuating the pathogen in chick fibroblast (5,20). This is while the Jeryl Lynn strain of mumps is produced owing to this concept by inoculating it into specific pathogen free (SPF) chicken embryonic fibroblasts (21) and cell cultures of chick embryo (20,22).…”
Section: Attenuation By Loss Of Genetic Poolmentioning
confidence: 99%